Development of GEBI: “game edukasi berbasis IoTs” for fashion students at vocational senior high school - Nasrillah, Yusrin; Yavie, Evania; Aini, Nurul; Krisnanda, Thiessa; Asfia, Yunita; Ubaidah, Siti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Research sought create and authenticate educational game GEBI (Game Edukasi Berbasis IoTs) targeted numeracy literacy enhancement in Pattern Making for Grade 10 students at SMKN 7 Malang studying Fashion Design and Production as part Phase E of Merdeka Curriculum. The game development followed the ADDIE model with validation as primary focus. The educational game GEBI developed through Liveworksheet platform which includes features such as login access, level-based contextual questions, multiple-choice tasks, instant feedback and progress tracking. This approach used constructivist pedagogy to develop essential numeracy skills including unit conversion and measurement interpretation to enable effective problem-solving for basic pattern drafting. Validation included participation from 30 students alongside two educational media experts and two subject matter experts. Questionnaire with 4-points Likert scale evaluated visual design together with pedagogy, content accuracy, examined interactivity and usability. Researchers applied quantitative analysis through percentage-based feasibility measures which required scores of 61% or higher. The feasibility study revealed GEBI's high feasibility after achieving total score of 93% which included 88% from media experts and 98% subject matter experts. The brief academic calendar created a limited development time which presented a major challenge. This research advances digital learning innovations in vocational education and recommends further studies evaluating success.